Life on an island: the phylogenetic placement of Loveridgeana and Afrotropical Sphaerophoria (Diptera: Syrphidae) inferred from molecular characters. Issue 1 (4th December 2020) - Mengual, Ximo; Ståhls, Gunilla; Skevington, Jeffrey H.
Abstract : Phylogenetic relationships of the Sphaerophoria lineage ( Sphaerophoria Le Peletier & Audinet-Serville and related genera) were inferred based on molecular characters, with the specific aim to infer the phylogenetic placement of the Afrotropical Sphaerophoria species and Loveridgeana beattiei van Doesburg & van Doesburg. Three molecular markers were used, i.e., the mitochondrial protein-coding gene cytochrome c oxidase subunit I (COI) and the nuclear 28S and 18S ribosomal RNA genes. The Sphaerophoria lineage genera Exallandra Vockeroth and Loveridgeana were resolved within the genus Sphaerophoria, and the Indomalayan Eosphaerophoria Frey was placed sister to Citrogramma Vockeroth, both related to a large species radiation from the New World. Fazia Shannon and Allograpta Osten Sacken were recovered as non-monophyletic. Our results recovered two different Fazia clades with dissimilar natural history resulted from our analyses, and Allograpta species were resolved into two clades, one with Nearctic and Neotropical species and a second clade with species from Oceanian, Indomalayan and Afrotropical Regions. Exallandra is considered a subgenus of Sphaerophoria, S . ( Exallandra ) stat. rev., and Sphaerophoria cinctifacies (Speiser) n. comb. a member of this subgenus together with S. loewii Zetterstedt. A new Sphaerophoria subgenus is designated S. ( Loveridgeana ) stat. rev. to include S. beattiei n. comb. and the South African species, i.e., S. quadrituberculata Bezzi, S. retrocurva Hull, and S . aff. retrocurva . Based on their phylogenetic distinctiveness, functional traits, and ecological relevance we do recommend further ecological study and protection efforts for this Afrotropical group of pollinators.